The Network of Inflammatory Mechanisms in Lupus Nephritis - Nozaki, Yuji (Frontiers in Medicine, 2020)
Many signaling pathways have been shown to be involved in the progression of kidney disease in humans and in animal models, usually due to persistent activation of these pathways. Perhaps the best well known of such pathways include certain inflammatory cytokines and protein kinase pathways, such as protein kinase C and mitogen-activated kinase pathways, which lead to cellular growth and fibrosis, and those, such as angiotensin II and transforming growth factor-β signaling pathways, which enhance fibrosis leading to kidney scarring. Therefore, challenges in kidney disease include continuing to improve the advances in pathogenesis and molecular biology, and novel therapeutic options. This Research Topic aims to update important aspects regarding kidney disease such as diabetic nephropathy, lupus nephritis, and vasculitic nephritis (i.e. anti-neutrophilic cytoplasmic antibodies associated vasculitis). We also aim to discuss new disease targets, description of potential pathologic pathways, promising therapeutic approaches from basic science to clinical work.